CONCEPT OF SHUKRA DHATU - Patel Vishnu; Sasmal Gitanjali; Kumar Ashok (International Journal of Applied Ayurved Research, 2020)
Individual Purusha is consists of three Dosha. Seven Dhatu and three Mala which are the primary basics of the living body. Sukra Dhatu is considered as best among all seven Dhatus. Shukra is white, pure, excellent Dhatu which is located in entire body. Shukra is the substance responsible for systematic body activities including metabolic functions and part of which comes out of the body at the time of sexual act and perform specific functions of reproductions. Sperm along with spermatic fluid and male sex hormone are also one part of Shukra Dhatu. At times, two distinct terms are used to describe the male and female seed. Shukra universally applies to sperm